Flavonoids from Nigerian indigenous medicinal plants and their bioactivities: A review - J.I. Achika; A.J. Yusuf; R.G. Ayo; D.U. Liman (Elsevier, 2023)
Introduction: Medicinal plants are used individually or in combination in Nigerian Traditional Medicine for the treatment of myriad of ailments. This review focus on flavonoids isolated from Nigerian indigenous medicinal plants and their pharmacological activities Methods: Scientific databases such as SciFinder, Medline, Google Scholar, and ScienceDirect were accessed for literature on flavonoids isolated from Nigerian medicinal plants. The Names and authors of plant species were authenticated using the International Plant Name Index. Results: Sixty-nine (69) medicinal plants have been currently reviewed, from which two hundred and fifty-eight (258) bioactive flavonoids have been reportedly isolated which fall within the flavones, flavanones, flavanols, flavanonols, anthocyanidins, chalcones and bioflavonoids. In vivo and in vitro experiments validating the bioactivities of the isolated flavonoids were also reviewed viz: Osteogenic potential, antioxidant, anti-inflammatory, antimicrobial, antibacterial, anticancer, antidiabetic, trypanocidal, antimalarial, cytotoxicity, antiproliferative, nephrotoxicity, potent immunostimulatory, xanthine oxidase inhibitory activity and immunomodulatory effects. Conclusions: From this review, it can be inferred that Nigerian plants are a great source of novel flavonoid compounds and thus, flavonols being the major constituents of the medicinal plants in Nigeria, can be studied further for possible development into nutraceuticals against diabetes, malaria and other several metabolic diseases. This study provides literature on phytochemistry, and biological evaluations and creates a scientific justification for the use of these plants in Nigerian Herbal Medicine.